2014
DOI: 10.1111/jan.12609
|View full text |Cite
|
Sign up to set email alerts
|

A cross‐sectional survey of factors related to inpatient assault of staff in a forensic psychiatric hospital

Abstract: Physical violence by patients was a pervasive threat for a high proportion of staff. Frequent conflict interactions with volatile patients contributed the most risk, but reactivity to conflict was a dynamic risk factor. The strain associated with assault risk and stress reactivity could be prospectively mitigated by resilience enhancement programming for staff.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
66
2
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(80 citation statements)
references
References 67 publications
7
66
2
5
Order By: Relevance
“…In the presence of conflict, individuals who reported higher levels of agreeableness were more likely to experience negative affect than those who were less agreeable. Kelly, Subica, Fulginiti, Brekke, and Novaco (2015), with a slightly larger sample overlapping that of the present study, found that patient-on-staff assault was associated with social conflict, but that relationship was moderated by stress reactivity in a curious way. Staff at the highest risk for patient assault were those who were frequently exposed to conflict but were also less reactive to conflict.…”
Section: Stress Reactivity To Assault and Conflictcontrasting
confidence: 47%
“…In the presence of conflict, individuals who reported higher levels of agreeableness were more likely to experience negative affect than those who were less agreeable. Kelly, Subica, Fulginiti, Brekke, and Novaco (2015), with a slightly larger sample overlapping that of the present study, found that patient-on-staff assault was associated with social conflict, but that relationship was moderated by stress reactivity in a curious way. Staff at the highest risk for patient assault were those who were frequently exposed to conflict but were also less reactive to conflict.…”
Section: Stress Reactivity To Assault and Conflictcontrasting
confidence: 47%
“…Apesar de outras pesquisas terem encontrado associação entre maior tempo de experiência profissional e menor chance de passar pela experiência de ser agredido fisicamente 8,14 , este estudo encontrou relação inversa. Isso talvez possa ser explicado por: maior nível de estresse entre profissionais com maior tempo de experiência 2 ; mudança recente no perfil dos pacientes, passando do portador de patologias tradicionais a um maior número de dependentes quí-micos, o que exige novas estratégias de abordagem para as quais os profissionais participantes podem não estar preparados 13 , ou menor tolerância a qualquer ato de agressão, o que precipita a ocorrência de novos eventos 17 .…”
Section: Discussionunclassified
“…As pesquisas realizadas em hospitais psiquiá-tricos de outros países apresentam diversos fatores como determinantes da violência nestas instituições, geralmente relacionados ao perfil do paciente, como idade, gênero, presença de sintomas psicóticos e uso de álcool e outras drogas 7,8 .…”
Section: Introductionunclassified
See 1 more Smart Citation
“…The importance of strengthening the ability to manage demanding situations has only recently been acknowledged. Fostering coping skills and resilience are now recommended components of AM training (30,31). Although there is ample guidance for designing AM training, scientific evidence proving its actual benefits is limited (32): a number of literature reviews synthesizing evidence on the effect of AM training point to predominantly low quality of research (33)(34)(35)(36)(37).…”
Section: Introductionmentioning
confidence: 99%